The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1007/bf00015032
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence analysis of a cDNA encoding a Brazil nut protein exceptionally rich in methionine

Abstract: The primary amino acid sequence of an abundant methionine-rich seed protein found in Brazil nut (Bertholletia excelsa H.B.K.) has been elucidated by protein sequencing and from the nucleotide sequence of cDNA clones. The 9 kDa subunit of this protein was found to contain 77 amino acids of which 14 were methionine (18%) and 6 were cysteine (8%). Over half of the methionine residues in this subunit are clustered in two regions of the polypeptide where they are interspersed with arginine residues. In one of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…Also referred to as 1.7S albumins or napin-like proteins (8,41), they are water-soluble seed storage proteins, present in multiple isoforms and composed of two polypeptide chains of 8 to 12 and 3 to 5 kD, linked by disulfide bridges (2,16,23). 2S albumin genes are encoded by multigene families (36) and are of particular interest because cDNA (1,8,13) and gene cloning experiments (23,30) have shown that the protein is formed from large precursors which undergo extensive proteolytic processing, including signal peptide cleavage, removal of an additional amino-terminal fragment as well as an internal segment, and elimination of a few carboxy-terminal residues (8,16). The exact processing sites have been determined for napin (16), Brazil nut 2S (1, 2, 13) and Arabidopsis thaliana 2S (23).…”
mentioning
confidence: 99%
“…Also referred to as 1.7S albumins or napin-like proteins (8,41), they are water-soluble seed storage proteins, present in multiple isoforms and composed of two polypeptide chains of 8 to 12 and 3 to 5 kD, linked by disulfide bridges (2,16,23). 2S albumin genes are encoded by multigene families (36) and are of particular interest because cDNA (1,8,13) and gene cloning experiments (23,30) have shown that the protein is formed from large precursors which undergo extensive proteolytic processing, including signal peptide cleavage, removal of an additional amino-terminal fragment as well as an internal segment, and elimination of a few carboxy-terminal residues (8,16). The exact processing sites have been determined for napin (16), Brazil nut 2S (1, 2, 13) and Arabidopsis thaliana 2S (23).…”
mentioning
confidence: 99%
“…Ewan (1996) tested 62 patients for cross-reactivity to six nuts: peanut, Brazil nut, almond, hazelnut, walnut, and cashew nut, but did not report the species involved in each treatment. Table based on references (Altenbach et al 1987;Arshad et al 1991;Fernandez et al 1995;Tariq et al 1996;Marinas et al 1998;Moneret-Vautrin et al 1998;Sutherland et al 1999;Teuber and Peterson 1999;Teuber et al 1999Teuber et al , 2003Diaz-Perales et al 2000;Bannon et al 2001;Poltronieri et al 2002;Wang et al 2002;de Leon et al 2003;Roux et al 2003;Asero et al 2004;Lerch et al 2005;Crespo et al 2006;Benito et al 2007;Willison et al 2008;Ahn et al 2009;Breiteneder 2009;Garino et al 2010;Allergen.org 2014). VOLUME 33 (2) Tree Nut Allergenscross-reactivity, though additional comparisons are needed to investigate this hypothesis.…”
Section: Cross-reactivity Is Not Associated With Sequence Similaritymentioning
confidence: 99%
“…These proteins have been extensively studied since they may be useful for the improvement of the nutritional value of crops. These studies have concentrated on gene characterization [2][3][4] and expression of Brazil nut 2S albumins in transgenic plants [5][6][7][8]. In addition, studies on 2S gene promoter structure [9] and post-translational processing [10] have been performed.…”
Section: Introductionmentioning
confidence: 99%